Factors determining the succesful performance of Baitul Maal Wat Tamwil in Indonesia : an empirical investigation - Dawami, Qasdan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
aitul Maal wat Tamwil (BMT) has been considered a leading Islamic microfinance institution in Indonesia. The main objective of the establishment is to eradicate poverty and improve the social welfare of society by assisting the poor and micro-enterprises financially. However, despite the success story, several BMTs suffered failure and bankruptcy due to their inability to resolve existing problems such as a lack of capital structure of funding, inadequate human resources, and a lack of governance. Furthermore, the members of the BMT have relatively low income and a lack of business management skills. Hence, the purpose of the study is to determine key factors influencing the successful performance of the BMT in Indonesia. The study also aims to help the BMT managers reduce the risk of failure and enhance the chance of success in their business. This study is a field research with a mixed-method approach. In addition, this study employed triangulation as a data collection method through conducting semi-structured interviews with 3 directors of the BMTs and administering questionnaires to 225 employees of the BMTs. The quantitative data are analysed using several statistical test analyses such as reliability analysis, ANOVA, multiple regression analysis, F-test, and T-test, while the qualitative data use codification and thematic analysis. The findings exhibited five significant issues faced by the BMT in the operation and development in Indonesia, namely a lack of capital, loose regulations, inadequate human resources, a lack of understanding of Islamic transaction contracts, and a lack of financial technology. Moreover, the findings also pointed out that there are only three key factors of the successful performance of the BMT in Indonesia, namely the capital structure of funding, human resource adequacy, and product innovation. This study recommends the BMTs managers to keep practicing the seven principles of the BMTs, provide regular seminars and training programs to the staff and members, and provide more innovative products to fulfil the specific needs of the society.